Top-down effects of fire salamander larvae (Salamandra salamandra) on benthic organisms differs between habitat types - Christoph Ptatscheck; Laura Schulte; Jonathan Berger; Barbara A. Caspers (Scientific Reports)
Abstract Fire salamander larvae are top predators in limnic habitats and feed on a wide spectrum of prey. For our study, we hypothesized that the larvae have a top-down effect on meiofauna, but that this effect varies depending on the habitat the larvae originate from. Therefore, we collected larvae from ponds and streams and placed them individually into microcosms with sediment and benthos. After either one week or two weeks, we removed the larvae and counted the number of nematodes, oligochaetes, and rotifers. Already after week one, the abundance of meiofauna was significantly reduced, as was their biomass. Nematodes were more strongly reduced by pond larvae during this week, while oligochaetes were primarily affected by stream larvae but not by pond larvae, regardless of the sampling time. The rotifers were reduced by larvae from both habitats, but only during the first week and not during the second week. Our findings suggest that fire salamander larvae not only have a top-down effect on pelagic or macrobenthic organisms, as often described in other studies, but can also shape the community of small endobenthic organisms. Depending on habitat-specific adaptations in feeding behavior, morphology, or physiology, these effects can vary.